Influence of Stress Sensitivity on Water-Gas Flow in Carbonate Rocks - Shuaishi Fu; Lianjin Zhang; Yingwen Li; Xuemei Lan; Roohollah Askari; Junjie Wang; Wen Wen; Xinze Li; Shaobin Cai; Ke Wang; Jie Liu; Yushu Wang; et al. (Geofluids)
Carbonate reservoirs significantly contribute to exploitation. Due to their strong heterogeneity, it is of great significance to study core seepage capacity and gas-water two-phase flow of reservoirs with various pore structures under different stresses for productivity prediction, gas reservoir development, and reservoir protection. We utilize micrometer-resolution X-ray tomography to obtain the digital rocks of porous, fractured-porous, and fractured-vuggy carbonate rocks during pressurized process and depressurization. The Lattice Boltzmann method and pore network model are used to simulate the permeability and gas-water two-phase flow under different confining pressures. We show that at the early stage of pressure increase, fractures, vugs, or large pores as the main flow channels first undergo compaction deformation, and the permeability decreases obviously. Then, many isolated small pores are extruded and deformed; thus, the permeability reduction is relatively slow. As the confining pressure increases, the equal-permeability point of fractured-porous sample moves to right. At the same confining pressure, the water saturation corresponding to equal-permeability point during depressurization is greater than that of pressurized process. It is also proved that the pore size decreases irreversibly, and the capillary force increases, which is equivalent to the enhancement of water wettability. Therefore, the irreversible closure of pores leads to the decrease of permeability and the increase of gas-phase seepage resistance, especially in carbonate rocks with fractures, vugs, and large pores. The findings of this study are helpful to better understand the gas production law of depletion development of carbonate gas reservoirs and provide support for efficient development.